Tanggung Gugat Pelaku Usaha Jasa Laundry - Fasrum F Kastella; Teng Berlianty; Theresia Nolda Agnes Narwadan (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Laundry services are needed not only by households but also by students and society in general. It is currently proven to be found around settlements and its surroundings. The community's need for laundry services must be balanced with the responsibilities of business actors in maintaining the quality of service and ensuring that consumers do not lose, scarcity or damage to the clothes being laundered. As already regulated in Article 4 UUPK No 8 of 1999. The problem in this research is how the position of the parties in the laundry service business activities and what are the goals of the laundry service business actors as a result of default. The purpose of this research is to analyze and assess how the position of the parties in laundry service business activities and what are the goals of laundry service business actors due to default. The research method used is normative juridical, the problem approach used is the statutory approach (statue approach) and the conceptual approach (conceptual approach), the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials is a literature study. The results of this study indicate the position of the parties in the laundry service business activities as business actors and the goals of the laundry service business actors due to default, the rights of consumers who use laundry services are not fulfilled by the laundry service business actors, so that the consumers who have experienced losses should or default caused by the laundry service business actor, then the laundry service business actor must be held accountable for actions that result in default on consumers.